Christine [videorecording (DVD)] - Hall, Rebecca, 1982-; Hall, Michael C., 1971-; Letts, Tracy, 1965- (Sony Pictures Home Entertainment, 2017)
The story of a woman who finds herself caught in the crosshairs of a spiraling personal life and career crisis. Christine, always the smartest person in the room at her local Sarasota, Florida news station, feels like she is destined for bigger things and is relentless in her pursuit of an on-air position in a larger market.